2015
DOI: 10.17987/icfj.v1i1.15
|View full text |Cite
|
Sign up to set email alerts
|

The significance of rate pressure product in heart failure patients

Abstract: <p><span>Introduction: </span>The rate pressure product (RPP) is a strong determinant of myocardial oxygen consumption, and relates strongly to important indices for morbidity and cardiovascular mortality. Its significance in Black-African subjects with heart failure (HF) has however not been well described. This study therefore aimed to assess the significance of RPP among admitted HF patients in 2 Nigerian centres.</p><p><span>Methods: </span>Admitted HF patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…This research is different from the study conducted by Karaye et al (2015), where RPP is not associated with hospital mortality but is strongly associated with interventricular septal thickness (IVST), left ventricular posterior wall thickness (LVPWT), and NT-BNP, which are risk factors for MACE events. [36].…”
Section: Resultscontrasting
confidence: 89%
“…This research is different from the study conducted by Karaye et al (2015), where RPP is not associated with hospital mortality but is strongly associated with interventricular septal thickness (IVST), left ventricular posterior wall thickness (LVPWT), and NT-BNP, which are risk factors for MACE events. [36].…”
Section: Resultscontrasting
confidence: 89%
“…[32] In the present study, we found a prevalence of high RPP of 59.9%, which is similar to the value we previously found (65%) in HF patients with various etiologies including PPCM. [20] In both studies, however, it was not associated with poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 82%
“…High RPP was defined as values >10,000. [20] Electrocardiography and echocardiography were carried out on each subject using standard criteria and methods. [21,22] The patients were re-evaluated at three-monthly interval and echocardiogram repeated six monthly to assess for the presence and extent of ventricular myocardial remodeling and changes in the size of the cardiac chambers.…”
Section: Methodsmentioning
confidence: 99%
“… 6 The RPP, defined as heart rate multiplied by blood pressure, is a convenient and simple reference index to indirectly reflect cardiac work load and myocardial oxygen consumption and it relates strongly to important indices for cardiovascular morbidity and mortality in patients with myocardial ischemia. In the study by Karaye KM, 9 there was a close relationship between RPP and heart failure with indices for LV wall tension including interventricular septal thickness, LV end-diastolic dimension and N-terminal B-type natriuretic peptide level. Development of heart failure leads to hemodynamics disturbance and excessive sympathetic activity.…”
Section: Discussionmentioning
confidence: 94%
“… 6 , 7 RPP is strongly related with cardiovascular risk in hypertension patients 8 and has a close relationship with heart failure patients. 9 For coronary artery disease (CAD) patients, RPP is associated with myocardial perfusion imaging findings using gated single photon emission computed tomography imaging with dipyridamole stress and the occurrence of ischemic events has been shown to be related closely to increases in the RPP. 8 , 10 However, the usefulness of RPP in risk stratification for occurrence of short- and long-term mortality, has not been established in ACS patients undergoing primary PCI, which is the subject of the present study.…”
Section: Introductionmentioning
confidence: 99%